Earthworms from natural and managed ecosystems in Southern Bahia, Brazil - Da Silva, Elodie; Santos, Alessandra; Nadolny, Herlon S.; Bartz, Marie L.c.; James, Samuel W.; Brown, George G. (Zootaxa, 2023)
The earthworms (Crassiclitellata) of the Northern Atlantic Forest region are poorly known, and many new species are expected to be found in the region. Hence, quantitative and qualitative samples were taken in the Atlantic Forest region of southern Bahia State, Brazil, at eight sites to assess species presence and abundance in different land uses (forests, pastures, plantations). Earthworms were also qualitatively collected at an additional eight sites. Only one to two species per site were found in quantitative samples, while qualitative samples generally resulted in higher species recoveries, with highest richness observed at the native Atlantic Forest of Veracel in Porto Seguro. Pontoscolex corethrurus (Müller, 1857) was the dominant species at all sites and in most land use systems, probably favored by human migration and agricultural activities; it was only absent in one primary forest site where native Ocnerodrilidae species predominated. In total at least 14 species were found of which eight were new, belonging to the genus Rhinodrilus and three new genera in the Ocnerodrilidae family (Pauqueba, Parabauba and Diplomoela). Contrary to sites in Southern and Southeastern Brazil, where many native species belong to the Glossoscolecidae family, in southern Bahia, Ocnerodrilidae species tend to be more prevalent, occupying various habitats. More intensive sampling of these habitats, including surface litter, in and under fallen logs and dead tree trunks, under rocks, in bromeliad leaf tanks and deeper soil layers is essential in order to properly characterize earthworm communities in Brazilian Atlantic Forests.